2003
DOI: 10.1111/j.1654-1103.2003.tb02123.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed and seedling demography of invasive and native trees of subtropical Pacific islands

Abstract: Abstract. Bischofia javanica is an invasive tree of the Bonin Islands in the western Pacific, Japan. This species has aggressive growth, competitively replacing native trees in the natural forest of the islands. The aim of this study was to examine seed and seedling factors which might confer an advantage to the establishment of Bischofia over native trees. During a 5‐yr period we compared the demographic parameters of early life history of Bischofia and Elaeocarpus photiniae‐folius, a native canopy dominant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…In Hong Kong, Hau (1997) concluded that forest restoration by direct seeding would not be feasible due to rat (R. rattus and Niviventer fulvescens) predation of 12 plant species. Yamashita et al (2003) suggested that R. rattus may be facilitating the invasion of the nonnative tree Bischofia javanica in the Ogasawara Islands because R. rattus depredates the seeds of the dominant native tree Elaeocarpus photiniae-folius both before dispersal (27% -33% of the seed crop) and after dispersal (41% -100%). Several other studies of fruit and seed removal have occurred on Pacific islands that include R. rattus as part of the rodent community, but the particular rodent species responsible for such removals were not identified (e.g., Moles and Drake 1999, Uowolo and Denslow 2008, Meyer and Butaud 2009, Erwin and Young 2010, GrantHoffman et al 2010, Chimera and Drake 2011.…”
Section: Impact On Plant Communitiesmentioning
confidence: 99%
“…In Hong Kong, Hau (1997) concluded that forest restoration by direct seeding would not be feasible due to rat (R. rattus and Niviventer fulvescens) predation of 12 plant species. Yamashita et al (2003) suggested that R. rattus may be facilitating the invasion of the nonnative tree Bischofia javanica in the Ogasawara Islands because R. rattus depredates the seeds of the dominant native tree Elaeocarpus photiniae-folius both before dispersal (27% -33% of the seed crop) and after dispersal (41% -100%). Several other studies of fruit and seed removal have occurred on Pacific islands that include R. rattus as part of the rodent community, but the particular rodent species responsible for such removals were not identified (e.g., Moles and Drake 1999, Uowolo and Denslow 2008, Meyer and Butaud 2009, Erwin and Young 2010, GrantHoffman et al 2010, Chimera and Drake 2011.…”
Section: Impact On Plant Communitiesmentioning
confidence: 99%
“…Goats have also caused local extinctions and population declines in endangered plants, such as Lobelia boninensis and Crepidiastrum grandicollum, in the archipelago (Ono 1998). Furthermore, the introduced rat reportedly eats and/or damages the seeds, fruits, and twigs of many native plant species (Toyoda 2003;Watanabe et al 2003;Yamashita et al 2003;Abe 2007;Hashimoto 2010;Yabe et al 2010;Abe and Umeno 2011). Although reports on the negative impacts of introduced phytophagous insects on native plants are rare (Sugiura 2010a), the introduced weevil, Rhabdoscelus obscurus, reportedly damages the basal parts of leaves in the endemic palm Clinostigma savoryana (Karube et al 2008(Karube et al , 2009).…”
Section: Herbivorymentioning
confidence: 99%
“…The tall tree species B. javanica, which was introduced and planted in the Ogasawara Islands before 1905 as a forestry tree, has invaded native forests via bird-dispersed seeds (Shimizu 2003). Bischofia javanica has advantageous features in terms of competition for resources with other plants, which include rapid seedling and sapling growth, vigorous sprouting ability, shade-tolerant juveniles, and high fecundity (Yamashita et al 2000(Yamashita et al , 2003Shimizu 2003). Hence, B. javanica has gradually replaced native forests (Tanaka et al 2010).…”
Section: Interspecific Competitionmentioning
confidence: 99%
See 2 more Smart Citations